Physical and sportive education in the classic school systems (Fiep Bulletin - online, 2015)
Present day situation of school physical educations in Latin America. Physical education for the various school groups, according to age. Systems of physical education and sport in teaching programmes. Physical culture for adolescents in secondary schools. School physical education in Quebec.